The postmodern Bible - Aichele, George; Bible and Culture Collective (New Haven : Yale University Press, 1995)
The burgeoning use of modern literary theory and cultural criticism in recent biblical studies has led to stimulating - but often bewildering - new readings of the Bible. This book, argued from a perspective shaped by postmodernism, is at once an accessible guide to and an engagement with various methods, theories, and critical practices transforming biblical scholarship today. Written by a collective of cutting-edge scholars - with each page the work of multiple hands - The Postmodern Bible deliberately breaks with the individualist model of authorship that has traditionally dominated scholarship in the humanities and is itself an illustration of the postmodern transformation of biblical studies for which it argues. The book introduces, illustrates, and critiques seven prominent strategies of reading. Several of these interpretive strategies - rhetorical criticism, structuralism and narratology, reader-response criticism, and feminist criticism - have been instrumental in the transformation of biblical studies up to now. Many - feminist and womanist criticism, ideological criticism, poststructuralism, and psychoanalytic criticism - hold promise for the continued transformation of these studies in the future. Focusing on readings from both the Hebrew Bible and the New Testament, this volume illuminates the current multidisciplinary debates emerging from postmodernism by exposing the still highly contested epistemological, political, and ethical positions in the field of biblical studies.
Includes bibliographical references (p. 311-381) and index.
Keywords: Bible -- Hermeneutics; Postmodernism; Bible -- Criticism, interpretation, etc. -- History -- 20th century; Bible; Bible -- x; Christianity -- Hermeneutics